Foster Care of the Basic Network for the Protection of Children and Adolescents of Bizkaia. Evolution and context - Gonzalez Rodriguez, Mikel; Beloki Aristi, Nekane; Alonso Saez, Israel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article attempts to expose the evolution of residential care resources, beginning with the Franco dictatorship until today. We will try to explain how the resources through which help was given to minors in vulnerable situations were financed. Likewise, we will analyze the evolution of these resources until today. These resources have been professionalized over time and, today, provide specific responses to the different needs of children, adolescents and young people in the historic territory of Bizkaia.